Exploiting hybrid vigor to enhance survival and growth for whiteleg shrimp (Litopenaeus vannamei): A complete diallel cross experiment - Zhangwu Yang; Zhe Zhang; Guodong Wang; Zhongchi Huang; Weiwei You (Aquaculture and Fisheries)
Whiteleg shrimp (Litopenaeus vannamei) is an economically important cultured species that is extensively cultured in China. However, there is the potential for further optimization of its survival and growth traits that are key determinants of productivity in aquaculture. This study investigated the efficacy of hybridization, a genetic improvement technology leveraging hybrid vigor, as a strategy for enhancing these traits in L. vannamei. The study was conducted using a 4 × 4 complete diallel cross experiment involving four selected strains (5, 8, 9, and 10), with the aim of identifying potential crosses exhibiting hybrid vigor. The most suitable crosses were those between strains 8 and 9, where the mid-parent heterosis (H89) was 16.52% for survival and 18.93% for growth. Our findings revealed that most reciprocal hybrids displayed higher rates of survival than their inbred parents. Additionally, an age-dependent increase in the heterosis effect on weight was observed over mid-parents and single-parents in most hybrid offspring. These findings suggest that hybridization could be a promising approach to improving the survival and growth of whiteleg shrimp. Our crossing experiment has yielded novel genetic resources for shrimp breeding, ultimately enhancing the economic importance of whiteleg shrimp.